A phenomenology study of using Instagram applications in personal creativity in photography at SMAN 2 Cirebon students - Kharisma Zhuhriani, Isma; Cinthia Fitrianas, Adinda; Shafira, Khalasa (COMMICAST, 2022)
The development of communication technology today brings about a number of changes in human behavior. These changes include how to think, how to behave, and various other aspects. This study aims to identify the development of existence in adolescents today. With the development of online media, there are behavioral changes that are quite specific to individuals, especially in the way that individuals perceive or interpret themselves. Furthermore, currently there are applications such as Instagram that can display photos and videos, which depict individual self-images. Society, especially young people, among dynamic students, tend to be happy to express themselves through online media which are considered to increase their existence. In this paper, the research method used is a qualitative approach. The research subject was carried out on students of SMAN 2 Cirebon City. To collect data, the authors conducted interviews with informants. From the results of interviews and data collection, it was found that teenagers today like to use the Instagram application to share photos, such as selfies, food, and photography. Furthermore, the photos included in Instagram include photos of daily activities with their friends, in the form of selfies, including photography in the form of beautiful natural scenery.